Sistem Informasi Aplikasi Kasir Pada Koperasi RSCM Jakarta Pusat Berbasis Java - Reza Avrizal; Erdiyansyah Saputra; Siti Suaedah; Nasrulloh Isnain (FORMAT, 2022)
The progress of an agency or company can be seen from how to use computer technology as a tool in solving problems. This is very supportive in the operation of an agency or company, both small, medium and large companies in increasingly fierce business competition. In this case the application in question is the Cashier Application System at the Indonesian Employee Cooperative, RSCM Central Jakarta, which is located at Jln. Diponegoro no. 71 Central Jakarta. This cashier and report application was built based on needs analysis from KPRI RSCM. This application was built using the JAVA programming language (Desktop) using Netbeans as its IDE, and using the MySql database. The methodology used by the researcher is the Agile software development method. The data collection methods used in this study were closed interviews, observation, and review of decisions from stakeholders so that the data obtained were able to accommodate the needs and initiation of the application to be built. This application is tested using blackbox as a test of application functionality.